Character Formation Through Education: A Review of Educational Philosophy on Values and Virtue - Simbolon, Bintang R. (Khazanah Pendidikan Islam, 2024)
Character education has become the main focus in the modern education system as a response to the need to form strong values and virtues among students. Social transformation and technological advances have influenced methods and approaches in character education, demanding continuous adaptation from educational institutions. Diversity in the classroom and the challenges of integrating these values into an already dense curriculum add complexity to the effective implementation of character education. This research aims to explore the methodology, challenges, and effectiveness of implementing character education in the current education system. This research was conducted using descriptive qualitative methods, where data was obtained from analysis of literature relevant to the topic. The data collected is then analyzed in depth to gain a broader understanding of the dynamics and results of character education. The conclusion of this research shows that character education is essential in forming individuals who not only excel academically but also have high moral integrity. Collaboration between teachers, parents, and the wider community has proven vital in strengthening character education. Apart from that, adaptation to social and technological changes is also needed to maintain the relevance and effectiveness of character education. Continuous and adaptive evaluation of character education programs is needed to ensure success in facing emerging challenges. Ultimately, effective integration of character education into the curriculum requires a holistic and inclusive approach to addressing diversity and complexity in the classroom.